Health related quality of life of women with cervical cancer Calidad de vida relacionada a la salud de mujeres con cáncer de cuello uterino Qualidade de vida relacionada à saúde de mulheres com câncer de colo uterino - Wanessa Cassemiro Fernandes; Miako Kimura (Universidade de São Paulo, 2010)
This cross-sectional study aimed to evaluate the health related quality of life (HRQoL) of women with cervical cancer and to identify predictors of quality of life. Between November 2008 and February 2009, 149 women were interviewed. The instrument Functional Assessment of Cancer Therapy-Cervix Cancer (FACT-Cx) was used to assess HRQoL and, in general, the scores obtained indicated positive evaluation. The items that showed negative evaluation were: "I am interested in sex", "I feel sexually attractive", "I am afraid to have sex" and "My vagina feels too narrow or short". In multiple linear regression analysis, using the backward method, of the 18 independent variables, eight were predictive of HRQoL. Self-perceived health status was the most influential factor. Special attention should be given to the sexual dysfunctions of these women after radiotherapy. Este estudio, de corte transversal, tuvo como objetivos evaluar la calidad de vida relacionada a la salud (CVRS) de mujeres con cáncer de cuello uterino e identificar los factores de predicción de calidad de vida. Fueron entrevistadas 149 mujeres, en el período de noviembre de 2008 a febrero de 2009. El instrumento Functional Asesment of Cancer Therapy-Cervix Cancer (FACT-Cx) fue utilizado para evaluar la CVRS y, de forma general, los puntajes obtenidos indicaron evaluación positiva. Presentaron evaluación negativa los ítems: "tengo interés en sexo", "me siento sexualmente atrayente", "tengo miedo de tener relaciones sexuales" y "siento la vagina estrecha o demasiada corta". En el análisis de regresión linear múltiple, por el método backward, de las 18 variables independientes, ocho fueron factores de predicción de CVRS. La autopercepción del estado de salud fue el factor de mayor influencia. Atención especial debe ser dada a las disfunciones sexuales de esas mujeres después de la radioterapia. Este estudo, de corte transversal, teve como objetivos avaliar a qualidade de vida relacionada à saúde (QVRS) de mulheres com câncer de colo uterino e identificar os fatores preditores de qualidade de vida. Foram entrevistadas 149 mulheres, no período de novembro de 2008 a fevereiro de 2009. O instrumento Functional Assessment of Cancer Therapy-Cervix Cancer (FACT-Cx) foi utilizado para avaliar a QVRS e, de forma geral, os escores obtidos indicaram avaliação positiva. Apresentaram avaliação negativa os itens: "tenho interesse em sexo", "sinto-me sexualmente atraente", "tenho medo de ter relações sexuais" e "sinto a vagina estreita ou curta demais". Na análise de regressão linear múltipla, pelo método backward, das 18 variáveis independentes, oito foram preditoras de QVRS. A autopercepção do estado de saúde foi o fator de maior influência. Atenção especial deve ser dada às disfunções sexuais dessas mulheres após a radioterapia.